PENGARUH BUKTI FISIK, KENDALA, DAYA TANGKAP, JAMINAN DAN EMPATI TERHADAP NASABAH DALAM MENGAMBIL PEMBIAYAAN DI PT. WOM FINANCE KLATEN - mulyatun, sri; wasiati, hera; sudarmanto (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2024)
The goal of this study is to examine customer satisfaction with the services provided at PT. WOM FINANCE KLATEN which influences customer decisions in taking credit or financing from the company. In this study, the researcher only limited the variables Reliability, Responsiveness, Assurance and Empathy and the dependent variable was customer financing decisions at PT. WOM Finance Klaten. Data analysis per variable and analysis of the influence of variables from each answer obtained from the questionnaire answers which consist of the dependent variable. The sampling in this study used a random sampling technique, meaning a random sampling technique involving the company's customers themselves. Data were analyzed using Validity Test, Reliability Test, Multiple Linear Regression, Hypothesis Testing, Determination Coefficient and with the help of SPSS (Statistical Package for the Social Sciences) software. Hypothesis results show that the questionnaire results for each variable are declared valid, reliable and interrelated.